Emerging collaborative practice in the community : the San Juan, Batangas Interdisciplinary Approach (IDA) experience - Urbano-Canuto, Florinda
A discipline is an academic branch of knowledge such as medicine, nursing, physical therapy, occupational therapy, nutrition, etc. Interdisciplinary means that two or more disciplines work or learn together to solve a problem or gather information. Interprofessional describes the relationship between various disciplines as they purposely interact to work together to achieve a common goal and it is when students from two or more professions learn about, from and with each other to enable effective collaborations and improve health outcomes whole interprofessional collaborative practice is when multiple health workers from different professional backgrounds work together with patients, families, carers and communities to deliver the highest quality of care" (WHO, 2010) Since it was declared that last 2008 that San Juan, Batangas be a common site for community rotation within the different colleges of the University of the Philippines-Manil, the IDA team then involved students and faculty from different disciplines in the University. The activities included patient care, training of barangay health workers or other special projects in the barangay.
The Filipino Family Physician, 2013 51 (1) pages 29-35
Keywords: Interdisciplinary Studies; Intersectoral Collaboration